ANALISA KELAYAKAN FINANSIAL PRODUKSI JAMU KUNYIT ASAM SKALA RUMAH TANGGA (STUDI KASUS DI DESA JETAK PROGRAM KKNT-MBKM) - Watang, Natalia D. Christy; Mushollaeni, Wahyu; Tantalu, Lorine (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
Jamu is a traditional medicine derived from plants which are processed into concoctions without the addition of chemicals. One of the herbal medicines that is widely known by the public is herbal turmeric tamarind. Herbal turmeric tamarind is a traditional drink whose raw materials are turmeric, tamarind and sugar. This tamarind turmeric herb can be categorized as an herbal drink that has health benefits. This research was conducted at the Process Engineering Laboratory, Tribhuwana Tunggadewi University, Malang, in April 2023. The analysis used in this study was qualitative analysis and quantitative analysis. For the business of the tamarind turmeric herbal product, it is said to be feasible, judging by the HPP of the tamarind and turmeric product, it is Rp. 2,911, the selling price of the tamarind and turmeric herbal product is Rp. 5,000 per bottle, BEP consists of two types, namely BEP units which are Rp. 22,725 and BEP prices which are Rp. 113.626.199, the RC Ratio is 1.72. The positive NPV is Rp. 389.722.401, the R/C ratio is 1.72. The IRR is 151% which is higher than the bank's interest rate depending on the NPV. PP is obtained for 239 days or 7 months 29 days shorter than the age of the business being carried out.